Interior design since 1900 - Massey, Anne, 1956- (2020)
"From the 19th-century Arts and Crafts movement to the present day, and from Art Nouveau and Bauhaus to hi-tech and green design, every style of interior design since 1900 is charted in this wide-ranging survey. Design in the 20th century saw an extraordinary evolution, with the emergence of professional interior designers and the growing appetite to redesign homes at frequent intervals. In recent decades the focus has been on sustainable design in public spaces such as offices, factories and ships. Anne Massey explores these developments in social, political, economic and cultural contexts. More than 200 illustrations of interiors from around the world, from William Morris's drawing room to a 21st-century aircraft, reveal the fundamental changes in taste and style from Art Deco to Pop and from the Streamline Moderne to Post-Modernism. This volume has been a classic introduction to the subject for almost thirty years. The new, fourth edition is brought up to date with a chapter on transnational design, encompassing mid-century modernist work in Singapore and Sri Lanka as well as very recent interiors for spaces as varied as luxury hotels in Dubai and a contemporary art museum in Cape Town. Anne Massey shows how a shared language of design and cutting-edge technology are reshaping interiors around the globe." --
Reforming Victorian taste -- The search for a new style -- The modern movement -- Art deco and the moderne -- The emergence of interior decoration as a profession -- Post-war modernism -- Consumer culture -- The post-modern era -- The sustainability of interior design -- Transnational interiors.
Previous edition: 2008.
Includes bibliographical references and index.
Keywords: 1900-1999; Interior decoration -- History -- 20th century; Interior decoration -- History -- 20th century; Interior decoration; Interieurkunst; History